PERSUASIVE COMMUNICATION STRATEGIES ON KARIER.MU DIGITAL TRAINING PLATFORMS - Priatna Priatna; Azhar Hutomo; Robbikal Muntaha Meliala; Romi Syahril (Sean Institute, 2023)
This research focuses on persuasive communication strategies in digital training media Karier.mu by applying the theory of four persuasive tactics: Powerful Persuasive Tactic, Persuasion in Its Infancy Stage, Technology Intensifies Persuasion, and Varying Levels of Acceptance of Persuasion. The aim of this study was to understand the influence of these tactics on user participation in career development. The research method used is descriptive qualitative by involving literature analysis, interviews and observations. The results showed that powerful persuasive tactics, such as creating a sense of urgency and evoking emotions, increased user participation. Users in the early stages of the career journey tend to be more receptive to persuasion. Technology, such as content personalization and progress measurement, amplifies persuasive messages. In addition, the acceptance rate of persuasion varies between users, emphasizing the importance of user segmentation. In conclusion, an effective persuasive communication strategy in Karier.mu includes a wide array of tactics to motivate users, provide guidance, utilize technology, and consider user acceptance. This research provides valuable insights for digital training media platforms in supporting users' career development.